2019
DOI: 10.1002/cta.2681
|View full text |Cite
|
Sign up to set email alerts
|

A new design strategy for DC/DC LLC resonant converter: Concept, modeling, and fabrication

Abstract: Summary In this paper, a new design procedure for LLC converter has been introduced. In fact, this method is a computer‐based design algorithm based on a numerical technique. In the process of designing, the value of the resonant element is obtained by solving the LLC converter fundamental equation. This converter will be controlled by using state feedback, such as output voltage variable. As a matter of fact, in a control system, the change of output voltage (because of load variation) will affect the switchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The nature of fixed-frequency modulation is to change the waveform of the square wave V ab input to the resonant tank. Using FHA and equivalent circuit method, the voltage transform gain M of the three modulations can be derived in Khosrogorji et al 9 as follows:…”
Section: Fixed-frequency Modulationmentioning
confidence: 99%
See 3 more Smart Citations
“…The nature of fixed-frequency modulation is to change the waveform of the square wave V ab input to the resonant tank. Using FHA and equivalent circuit method, the voltage transform gain M of the three modulations can be derived in Khosrogorji et al 9 as follows:…”
Section: Fixed-frequency Modulationmentioning
confidence: 99%
“…The waveform diagrams of three fixed‐frequency modulation methods, which are mentioned in Khosrogorji et al, 9 are shown in Figure 2. Each modulation strategy has a control angle α .…”
Section: Proposed Pfm and Avc Modulation Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…However, they are not recommended for high power application owing to high switch stress and lack of galvanic isolation. Among isolated battery charging topologies, many converters adopt the full bridge (FB) structure and its variants [8]. A hybrid FB converter integrated with a half-bridge (HB) structure or another FB structure on the primary side is presented in [9,10] where the reduction of conduction loss is realized due to the reduction of circulating current.…”
Section: Introductionmentioning
confidence: 99%